UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS BERITA DENGAN MENGGUNAKAN MEDIA BERBASIS TEKNOLOGI PADA SISWA SMP KELAS VIII GUDANG ARANG MERAUKE - Dina Mariana Br Tarigan (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The purpose of this community service activity is to improve the skills of writing news texts for Grade VIII students of junior high school by using technological media. This community service activity uses classroom action research. This activity was carried out at Gudang Arang Merauke Middle School involving 25 students. The stages used in cycles I and II were planning, implementation, and observation. The results of this activity showed that each cycle action experienced an increase. In cycle 1, the absorption power of 60.80% was obtained and the learning mastery reached 48%, while in the second cycle, student absorption reached 72.40% and student learning mastery reached 92%. Thus, the use of technological media can improve the ability to write news texts in class VIII students of SMP Gudang Arang.